Engineering the isobutanol biosynthetic pathway in Escherichia coli by comparison of three aldehyde reductase/alcohol dehydrogenase genes - Atsumi, Shota (Springer-Verlag, 2009)
Biofuels synthesized from renewable resources are of increasing interest because of global energy and environmental problems. We have previously demonstrated production of higher alcohols from Escherichia coli using a 2-keto acid-based pathway. Here, we have compared the effect of various alcohol dehydrogenases (ADH) for the last step of the isobutanol production. E. coli has the yqhD gene which encodes a broad-range ADH. Isobutanol production significantly decreased with the deletion of yqhD, suggesting that the yqhD gene on the genome contributed to isobutanol production. The adh genes of two bacteria and one yeast were also compared in E. coli harboring the isobutanol synthesis pathway. Overexpression of yqhD or adhA in E. coli showed better production than ADH2, a result confirmed by activity measurements with isobutyraldehyde.